Advanced Research on Glucosinolates in Food Products - Hanschen, Franziska S.; Rohn, Sascha (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Glucosinolate-containing foods, such as vegetables from the plant order Brassicales and its derivative products, are valued for their health-beneficial properties. The latter are linked to glucosinolate hydrolysis products, such as isothiocyanates.The book "Advanced Research on Glucosinolates in Food Products" collects the latest research on the impact of the whole food supply chain, including production, as well as domestic food preparation, on glucosinolates and the formation and chemistry of their breakdown products in vegetables and further foods. In this context, the consequences for human health are important, too. The book contains articles that cover research on the effect of pre-harvest factors on glucosinolates, their hydrolyzing enzymes, and the formation of volatile hydrolysis products. Further topics include the linkage between glucosinolates and sensory aspects, and the effects of food preparation and follow-up reactivity. Finally, research on the bioavailability and functional effects of isothiocyanates for human health is included.